How religious education policies work in practice: An empirical model from a school Qur’anic program in Indonesia - Muamar, Aam; Permana, Johar; Meirawan, Danny; Prihatin, Eka (Universitas Jambi, Indonesia, 2025)
This study investigates the implementation of religious education policies through an empirical analysis of a Qur'anic program (Sekolah Mengaji) in Indonesia. Using a qualitative research design, the study incorporates in-depth interviews with Islamic Religious Education teachers and observations in seven public junior secondary schools in Bandung regency. The findings reveal that religious education policy is enacted through a multi-layered process influenced by teacher agency, school culture, family involvement, and governance, rather than a direct translation of formal regulations. While policy implementation yielded positive outcomes in Qur'anic literacy and religious habituation, deeper character internalization remained inconsistent and context dependent. Key mechanisms such as teacher role modeling, interpersonal relationships, and instructional discretion were identified as central to linking policy intentions with daily practices. This study offers a model for understanding policy implementation variation across schools and contributes to the scholarship by focusing on the practical mechanisms that shape religious education policies.